Visual navigation: current research directions - Khomenko Olga V. (Архитектон)
The purpose of the article is to identify the key aspects that form the problems of wayfinding systems based on the systematization of approaches to the study and design of visual navigation. Works by Russian and foreign scientists who have made a significant contribution to the study of visual navigation systems and their impact on humans are analyzed. The evolution of the wayfinding – wayshowing – wayknowing concept is shown. The result of the study is a set of main aspects by which the problem of visual navigation can be structured.